Factors Influencing Adaptation of Rubber Plantation Farmers to Climate Change in Lower Southern Thailand - Thaiburi, Narid; Sinnarong, Nirote; Autchariyapanitkul, Kittawit; Nunthasen, Ke (Princess of Naradhiwas University Journal, 2021)
The objective of this research was to study factors for adaptation of rubber plantation farmers to climate change in the lower southern Thailand from 400 farmers. This research was choosen group of specific samples. The factors affecting the adaptation was used to analyze the relationship trough Ordered Logit models varied in order. The result revealed that factors affecting to adaptation of rubber plantation farmer consist of 7 variable such as bachelor’s degree, experience in rubber plantation, perception of information, suggestion from officer, perception and price of rubber increased. Farmers receive information will result in adapting to climate change. 82.50% significance at a 95% of the sample group of farmers.